Non-Small Cell Lung Cancer in Young Patients: An Analysis of Clinical, Pathologic and TNM Stage Characteristics Compared to the Elderly - Jin X; Zhao X; Liu X; Han K; Lu G; Zhang Y (Dove Medical Press, 2020)
Xin Jin, Xin Zhao, Xingsheng Liu, Ke Han, Gaojun Lu, Yi Zhang Thoracic Surgery Department, Xuanwu Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Yi ZhangThoracic Surgery Department, Xuanwu Hospital, Capital Medical University, Beijing, People’s Republic of ChinaTel +86-10-83922236Email zhangyi@xwhosp.orgPurpose: To compare clinicopathologic factors including tumor-node-metastasis (TNM) stage between young and elderly patients with non-small cell lung cancer (NSCLC).Methods: This retrospective study compared the following characteristics between 52 young patients with NSCLC (< 50 years of age) and 67 elderly patients with NSCLC (> 60 years): duration of symptoms before medical consultation, smoking index, family history of cancer, Ki-67 index, and pTNM stage. A binary logistic regression analysis was used to identify factors predictive of greater stage NSCLC (stage III/IV compared to stage I/II) within each age group.Results: The incidence of adenocarcinoma was higher in the young than in the elderly (P=0.006). Smoking index (P=0.002) and Ki-67 index (P< 0.001) were lower in the young than in the elderly. In young patients with NSCLC, delayed treatment (greater duration from symptoms to medical consultation, P=0.050) and active tumor proliferation (higher Ki-67 index, P=0.003) were predictive of more advanced cancer stage (III/IV), with only symptom duration being predictive of stage III/IV NSCLC among elderly patients. Among young patients, cough (P=0.021) and chest congestion (P=0.040) were the most significant warning symptoms of advanced-stage NSCLC.Conclusion: High tumor proliferation and delayed treatment are predictive of advanced NSCLC on presentation among young individuals. Early diagnosis by imaging, such as with the use of low dose computed tomography (LDCT), for young individuals with coughing and chest congestion over 1 month might be effectiveto improve prognosis and outcomes.Keywords: NSCLC, young adult patients, symptom assessment, Ki67